2014
DOI: 10.1590/s1516-14392014005000069
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid films with (trimethoxysilylpropyl) methacrylate (TMSM), poly (methyl methacrylate) PMMA and tetraethoxysilane (TEOS) applied on tinplate

Abstract: The tetraethoxysilane (TEOS) influences morphological and electrochemical properties of hybrid films by function of concentration. Moreover, the use of acetic acid as a catalyst in the sol enables a more complete hydrolysis of the silane precursors due to the fact that the acetic acid goes through a more complete ionization when in aqueous solution. The aim of this paper is to study the effect of the concentration of tetraethoxysilane (TEOS) on the protective properties of the film on tinplate substrate. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…The WCA were sensitive to many factors, mainly to surface chemical composition and roughness. The values observed for bare supports were 65° for Al and around 80° for TFS and ETP, which were comparable to those reported in the literature [35][36][37][38][39]. After coating, the initial WCA (WCAo) value increased slightly, i.e., about 6°…”
Section: Surface Wettability and Solubility Of Polyaleuritate Coatingssupporting
confidence: 88%
“…The WCA were sensitive to many factors, mainly to surface chemical composition and roughness. The values observed for bare supports were 65° for Al and around 80° for TFS and ETP, which were comparable to those reported in the literature [35][36][37][38][39]. After coating, the initial WCA (WCAo) value increased slightly, i.e., about 6°…”
Section: Surface Wettability and Solubility Of Polyaleuritate Coatingssupporting
confidence: 88%
“…The existence of active hydroxyl in SiO 2 repeatedly reunited to form sizeable aggregates and produces the above typical properties in a coating [19]. In a previous study by Kunst et al [20], higher amount of TEOS in a hybrid film was found to produce more roughness and led to very thin coating on deposition. Further, Surowska and Bienias [21] have studied the development of micro- cracks on the sol-gel deposited SiO 2 /TiO 2 coating on Ti-6Al-4V, they explained about the presence of non-homogeneous, less compact film over the substrate.…”
Section: Sem-edax Of Coating On Substratementioning
confidence: 92%
“…The tetraethoxysilane (TEOS) is a commonly silane used to form films that protect the metal of the corrosive attack. According to several authors 10,[12][13][14][15][16][17] the TEOS based hybrids film forms an homogeneous, compact and resistant physical barrier. These hybrid films protect and assure the integrity of metal substrates in corrosive media.…”
Section: Introductionmentioning
confidence: 99%